Identification of the characteristic parameters for gas pipe sections using the maximum likelihood method and least square method. Issue 3 (18th November 2021) - Chen, Huiyu; Qi, Da; Wang, Hui; Zhang, Qiang; Bu, Yaran; Zuo, Lili
Abstract: The pipeline efficiency factor ( E ‐value) and the overall heat transfer coefficient ( K ‐value) are, respectively, the characteristic parameters that describe the flow and heat transfer behavior of gas pipe sections. These parameters have a significant impact on the accuracy of the thermo‐hydraulic calculations of the gas flow processing. Hence, they should be investigated thoroughly. Due to various complex factors affecting the E ‐value and the K ‐value in operating the in‐service gas pipe sections, it is often difficult to calculate the two characteristic parameters accurately using physics‐based formulae. Based on quasi‐steady‐state historical operational data sets of the in‐service gas pipe section, the characteristic parameters are identified with the maximum likelihood method and the least square method, respectively. Besides, the characteristic parameters of the gas pipe section are derived from solving the inverse problem of the steady‐state thermo‐hydraulic calculations. Both methods are applied to an in‐service pipeline, and the two parameters are obtained from 144 historical operational data sets. By introducing the two parameters into the thermo‐hydraulic calculations for certain quasi‐steady‐state historical conditions in the same gas pipe section, the maximum relative errors occurred between the calculated results and the measured data are 2.91% and 2.66%, respectively. Additionally, the difference between the two methods is small, with a gap of 0.0037 W/(m 2 K) in K ‐value and 0.0206 in E ‐value. The proposed identification methods are extendable to provide adequate technical support for large‐scale gas pipeline networks. Abstract : Based on quasi‐steady‐state historical operating data of the in‐service gas pipe segment, the characteristic parameters (overall heat transfer coefficient and flow efficiency coefficient) of the pipe segment are identified with the maximum likelihood method and the least square method, respectively. The characteristic parameters of the pipe segment are obtained by solving the inverse problem of the steady‐state thermo‐hydraulic calculations.